Book of Tahkemoni : Jewish Tales from Medieval Spain. - Alharizi, Judah (Littman Library of Jewish Civilization, The, 2003)
Widely regarded as the crowning jewel of Heberew maqama literature (rhymed prose interspersed with verse) this book introduces a somewhat roguish protagonist, Hever the Kenite, often disguised as a teacher, beggar, adventurer, debater, or magician. Whether preaching, spinning history or fantasy, or working a crowd, Hever the Kenite is ever the consummate storyteller and wordsmith enlightening or astounding his listeners. The author displays great scope, moving from prayers to tales of battlefield carnage, from philosophic reflection to droll satire targeting the pompous, the ignorant and the m.